The Impact of China High Speed Rail on Regional Economic Development - Wang, Bingqing (Université d'Ottawa | University of Ottawa, 2018)
China has a vast territory with uneven resource distribution and unbalanced economic development. Agglomeration of urban centers have been taking place at a rapid rhythm over the last few decades. The capacity of railway transport is not sufficient to support national economic development, and the challenge is especially evident during festive seasons. There is an increasing demand for more carrying capacity to meet the growth in transport needs, and China's high-speed railway (HSR) system is designed to address transport demands. This paper analyzes the significance and impact of China’s HSR on regional economic development. It is shown that the HSR system has positive average treatment effects on regional economy during the construction period; however, the average treatment effects become negative during the operation period. It is suggested that the negative treatment effects were caused by the movement of workers and funds from less developed HSR cities to more developed HSR cities in search of higher returns. For this reason, the paper suggests that in order to fully enjoy the economic benefits brought by HSR, local governments should carry out policy reforms, such as increasing government spending on education and government spending on technology development to enhance local competitiveness.